RASIONALITAS INSTRUMENTAL DALAM KEBIJAKAN FISKAL: ANALISIS HILIRISASI SDA DAN PROGRAM MBG PERSPEKTIF JÜRGEN HABERMAS - Eugenius Besli; Wilhelmus Kelvin; Bartolomeus Da’o Lada (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the rational basis underlying the natural resource downstreaming policy and the Free Nutritious Meals (MBG) program in the Prabowo-Gibran administration, placing them in the perspective of Jürgen Habermas' instrumental rationality and communicative rationality. These two policies were chosen because they represent large-scale economic-political projects with significant fiscal implications and are concrete manifestations of the Asta Cita agenda. This study uses a qualitative method based on literature review by conducting a conceptual review and critical analysis of relevant academic literature, policy documents, and public reports. The results show that the downstreaming and MBG policies are predominantly guided by instrumental rationality oriented towards efficiency, accelerated investment, and expanded public spending. In the context of downstreaming, the emphasis on economic growth and industrial added value tends to overlook ecological risks and inequality in access to resources. Meanwhile, the implementation of the MBG program shows a centralistic pattern in budget management and a limited response to public criticism, even though this program absorbs significant fiscal resources. These findings indicate that fiscal policy management in both programs emphasizes technocratic calculations rather than participatory communicative deliberation. The dominance of instrumental rationality in high-cost policies has the potential to narrow the space for democratic legitimacy and weaken the quality of public financial management. Thus, this study emphasizes the importance of integrating fiscal efficiency and public deliberation in economic policy formulation so that development is not only technically rational but also democratically legitimate.